Pedagogical Integrations of the Bible in Organizing: A Qualitative Case Study from the Movement to End Poverty - Jessica Williams (Adult Education Research Conference, 2023)
Through cross-case analysis, this research explores how organizations in the movement to end poverty led by the poor in the U.S. integrate the Bible pedagogically in their organizing work.
Keywords: Bible; poverty; Social Movement Learning; Organized Poor; Pedagogy